Core features and inherent diversity of post-acute infection syndromes - Trautmann, Alain (Frontiers in Immunology, 2025)
Post-acute infection syndromes (PAIS), i.e., long-lasting pathologies subsequent to infections that do not properly resolve, have both a common core and a broad diversity of manifestations. PAIS include a group of core symptoms (pathological fatigue, cognitive problems, sleep disorders and pain) accompanied by a large set of diverse symptoms. Core and diverse additional symptoms, which can persist for years, exhibiting periods of relapses and remissions, usually start suddenly after an apparently common infection. PAIS display highly variable clinical features depending on the nature of the initial pathogen, and to an even larger extent, on the diversity of preexisting individual terrains in which PAIS are rooted. In a first part, I discuss biological issues related to the persistence of microbial antigens, dysregulated immune responses, reactivation of latent viruses, different potential self-sustained inflammatory loops, mitochondrial dysfunction, metabolic disorders in the tryptophan- kynurenin pathway (TKP) with impact on serotonin, and consequences of a dysfunctional bidirectional microbiota-gut-brain axis. The second part deals with the nervous system dependence of PAIS. I rely on the concept of interoception, the process by which the brain senses, integrates and interprets signals originating from within the body, and sends feebacks aimed at maintaining homeostasis. Interoception is central for understanding the origin of fatigue, dysautonomia, dysfunctioning of the hypothalamus-pituitary-adrenal (HPA) axis, and its relation with stress, inflammation or depression. I propose that all individual predispositions leading to self-sustained vicious circles constitute building blocks that can self-assemble in many possible ways, to give rise to both core and diverse features of PAIS. A useful discrimination between different PAIS subtypes should be obtained with a composite profiling including biomarkers, questionnaires and functional tests so as to take into account PAIS multidimensionality.